COMMUNITY EMPOWERMENT THROUGH MANGROVE PLANTING TO SUPPORT CLIMATE CHANGE ADAPTATION IN TANJUNG PASIR VILLAGE, TELUKNAGA DISTRICT, TANGERANG REGENCY - Reza Septian Pradana; Mikael Mardi; Anton Petrus W Nomleni (CV. Radja Publika, 2026)
Climate change has increased the vulnerability of coastal areas to abrasion, tidal flooding, and ecosystem degradation, necessitating adaptation efforts that actively involve the community. Tanjung Pasir Village, Teluknaga District, Tangerang Regency is one of the coastal areas facing these challenges and has the potential of mangrove ecosystems as a natural barrier in supporting coastal resilience. This Community Service activity aims to increase community knowledge, awareness, and participation in mangrove conservation as a climate change adaptation strategy through a community empowerment approach. The method used is the Community Empowerment Approach with the Participatory Learning and Action (PLA) principle which is implemented through four stages, namely preparation, education and socialization, participatory mangrove planting, and monitoring and evaluation. Data were obtained through participatory observation, documentation, and reflective discussions, then analyzed descriptively qualitatively. The results of the activity showed that the planting of 300 Avicennia and Rhizophora mangrove seedlings was successfully carried out with the involvement of students, lecturers, the community, the Tanjung Pasir Village Government, and the Tourism Awareness Group (Pokdarwis). This activity increased participants' understanding of the ecological function of mangroves, strengthened participation and collaboration between stakeholders, and fostered a shared commitment to maintaining the sustainability of mangrove areas. In addition to providing ecological benefits through coastal ecosystem rehabilitation, this activity also contributes to the achievement of the Sustainable Development Goals (SDGs), especially Goals 11, 13, 14, and 15. Thus, community empowerment through mangrove planting is an effective approach in supporting climate change adaptation while strengthening sustainable coastal area management.